Penerapan Model Project Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis Anak Usia Dini - Ani Handayani; Santa Idayana Sinaga (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to determine whether the application of the Project Based Learning Model Can Improve Critical Thinking Ability of 5 Year Old Children in Kindergarten Aisyiyah 2 Palembang. This type of research is classroom action research with two cycles. Research data through observation, observation and documentation. The subjects of the study were children from group B3 which consisted of 19 children consisting of 9 boys and 10 girls. The results showed that there was an increase in the average level of achievement in the development of critical thinking skills of children aged 5-6 years from pre-cycle to cycle I and to cycle II, namely that the pre-cycle score was 20.89 in the undeveloped category, then in the first cycle with a score of 29, 68 categories began to develop an increase of 8.79 while in the second cycle with a score of 40.05 the category developed very well, this indicates that the second cycle has increased by 10.37. Good learning is when collaborators provide project-based learning model learning activities because children will be stimulated and stimulated and feel happy when children are able to show exploratory activities and investigate animals in water, recognize the causes and effects of walking bicycles and draw conclusions from a natural disaster event so that Later, children will have good critical thinking skills for their future. Here children's critical thinking skills can be developed well if they get pleasant stimuli and motivations that build critical thinking skills in children.